Traumatic scleral wound dehiscence with filtering bleb formation after surgical repair of penetrating globe injury - Ozkaya, A; Alkin, Z; Acet, Y; Yigit, U (Nepalese Journal of Ophthalmology, 2013)
Backgropund: Filtering bleb formation after surgical repair of penetrating globe injury is a rare occurrence. Case: A 45-year-old male who had undergone surgical repair of a corneoscleral laceration 16 months earlier presented to emergency room after blunt trauma to the left eye. His best-corrected visual acuities were 20/20 in the right eye and 20/25 in the left. An anterior segment examination found a conjunctival filtering bleb formation on scarred sclera at superotemporal location near the limbus. Anterior chamber was slightly shallow and the Seidel test was negative. Intraocular pressures were 17 mm Hg in the right eye, 7 mm Hg in the left. The fundus examination revealed no abnormal findings. The patient was treated with topical aplication of a steroid and a cycloplegic drop during three weeks. After 16 months follow-up, the visual acuity remained unchanged with the persistence of filtering bleb. IOP was 8 mm Hg in the left eye. Follow-up examinations showed no complications related to trauma. Conclusion: Blunt ocular trauma can cause dehiscence in old scleral scars and subsequent filtering bleb formation. Nepal J Ophthalmol 2013; 5(9):136-137 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7843